A scientific and archaeological investigation of prehistoric glasses from Italy - Towle, Andrew C. (2002)
Ancient glasses are invariably complex materials, in which the specific chemical composition and microstructure capture aspects of their technologies. The chemical characterisation of glasses in specific archaeological contexts has given useful insight into the peculiarities of diverse glass-making technologies. In addition such studies generate more general information upon an important range of phenomenon, including the pyrotechnological milieu, empirical knowledge of sophisticated chemistry, organisation of production, access to significant raw materials and long-distance trade. This study examines a wide selection of glass artefacts recovered from archaeological contexts in Northern and Central Italy from approximately 1200 BC to 200 BC. The earliest material is from the Final Bronze Age, and extends the characterisation of an established glass type, which is unique to Europe and distinct from the contemporary technologies of the Eastern Mediterranean. Using a combination of X-ray fluorescence analysis, electron microprobe and scanning electron microscopy glass artefacts from a thousand-year period from the same region are investigated. The shifting technologies permit the discussion of localised production and importation of glass from elsewhere. The chemical analysis reveals a complex picture of glass production, which defies the expected pattern, and there is evidence for new compositional types, which may yet prove to be diagnostic of highly localised production. The changing compositions are discussed in relation to the broader archaeological context.